Protection of workers and third parties during the construction of linear structures - Vlčková, Jitka Laura; Venkrbec, Václav; Henková, Svatava; Chromý, Adam (IOP Publishing, 2017)
The minimization of risk in the workplace through a focus on occupational health and safety (OHS) is one of the primary objectives for every construction project. The most serious accidents in the construction industry occur during work on earthworks and linear structures. The character of such structures places them among those posing the greatest threat to the public (referred to as “third parties”). They can be characterized as large structures whose construction may involve the building site extending in a narrow lane alongside previously constructed objects currently in use by the public. Linear structures are often directly connected to existing objects or buildings, making it impossible to guard the whole construction site. However, many OHS problems related to linear structures can be prevented during the design stage. The aim of this article is to introduce a new methodology which has been implemented into a computer program that deals with safety measures at construction sites where work is performed on linear structures. Based on existing experience with the design of such structures and their execution and supervision by safety coordinators, the basic types of linear structures, their location in the terrain, the conditions present during their execution and other marginal conditions and influences were modelled. Basic safety information has been assigned to this elementary information, which is strictly necessary for the construction process. The safety provisions can be grouped according to type, e.g. technical, organizational and other necessary documentation, or into sets of provisions concerning areas such as construction site safety, transport safety, earthworks safety, etc. The selection of the given provisions takes place using multiple criteria. The aim of creating this program is to provide a practical tool for designers, contractors and construction companies. The model can contribute to the sufficient awareness of these participants about technical and organizational provisions that can help them to meet workplace safety requirements. The software for the selection of safety provisions also contains module that can calculate necessary cost estimates using a calculation formula chosen by the user. All software data conform to European standards harmonized for the Czech Republic.

The minimization of risk in the workplace through a focus on occupational health and safety (OHS) is one of the primary objectives for every construction project. The most serious accidents in the construction industry occur during work on earthworks and linear structures. The character of such structures places them among those posing the greatest threat to the public (referred to as “third parties”). They can be characterized as large structures whose construction may involve the building site extending in a narrow lane alongside previously constructed objects currently in use by the public. Linear structures are often directly connected to existing objects or buildings, making it impossible to guard the whole construction site. However, many OHS problems related to linear structures can be prevented during the design stage. The aim of this article is to introduce a new methodology which has been implemented into a computer program that deals with safety measures at construction sites where work is performed on linear structures. Based on existing experience with the design of such structures and their execution and supervision by safety coordinators, the basic types of linear structures, their location in the terrain, the conditions present during their execution and other marginal conditions and influences were modelled. Basic safety information has been assigned to this elementary information, which is strictly necessary for the construction process. The safety provisions can be grouped according to type, e.g. technical, organizational and other necessary documentation, or into sets of provisions concerning areas such as construction site safety, transport safety, earthworks safety, etc. The selection of the given provisions takes place using multiple criteria. The aim of creating this program is to provide a practical tool for designers, contractors and construction companies. The model can contribute to the sufficient awareness of these participants about technical and organizational provisions that can help them to meet workplace safety requirements. The software for the selection of safety provisions also contains module that can calculate necessary cost estimates using a calculation formula chosen by the user. All software data conform to European standards harmonized for the Czech Republic.
Protection of workers and third parties during the construction of linear structures
Keywords: OHS; third parties; linear structure; construction site; site safety; safety requirements; OHS; third parties; linear structure; construction site; site safety; safety requirements